2011
DOI: 10.2196/jmir.1600
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics and Motivations of Online Health Information Seekers: Cross-Sectional Survey and Qualitative Interview Study

Abstract: BackgroundMost households in the United Kingdom have Internet access, and health-related Internet use is increasing. The National Health Service (NHS) Direct website is the major UK provider of online health information.ObjectiveOur objective was to identify the characteristics and motivations of online health information seekers accessing the NHS Direct website, and to examine the benefits and challenges of the health Internet.Methods We undertook an online questionnaire survey, offered to users of the NHS Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
306
2
19

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 423 publications
(354 citation statements)
references
References 35 publications
27
306
2
19
Order By: Relevance
“…The qualitative data confirmed motivations [28,29] and enablers [30] found in previous research, and indicated that outcomes may be shaped by types of health information-seekers formed based on these motivations and enablers. This confirms that previously existing health behaviours translate to the online realm [28,31,32], as well as an emphasis on attitudes and skills as mediators for internet outcomes [17]. In that sense, online health resources become part of normal health practices, help-seeking, and everyday life information-seeking [33][34][35].…”
Section: Discussionsupporting
confidence: 83%
“…The qualitative data confirmed motivations [28,29] and enablers [30] found in previous research, and indicated that outcomes may be shaped by types of health information-seekers formed based on these motivations and enablers. This confirms that previously existing health behaviours translate to the online realm [28,31,32], as well as an emphasis on attitudes and skills as mediators for internet outcomes [17]. In that sense, online health resources become part of normal health practices, help-seeking, and everyday life information-seeking [33][34][35].…”
Section: Discussionsupporting
confidence: 83%
“…Az orvos-beteg találkozások során a betegek úgy ér zik, nem kapnak elég információt [25], ezért -ahogy a fentebb bemutatott nemzetközi és hazai statisztikák is mutatják -böngésznek az interneten, vagy kihasználják a web2.0 nyújtotta interaktív lehetőségeket. Itt fontos megjegyezni, hogy angol nyelvterületen és magyar nyelv területen a betegek által elérhető tartalom hitelessége erősen eltér.…”
Section: Döntési Mechanizmusokunclassified
“…This trend is not surprising, because patients and families (ie, "consumers") are increasingly turning to the Internet for health-related information. [6][7][8] Consumers now have multiple online venues for seeking information on the pricing of health care services, 9 as well as the quality of physicians.…”
mentioning
confidence: 99%